Progressive damage model of carbon-fiber reinforced polymer laminates under low-velocity impact loading / Mohd Suhairil Meon, Muhammad Faizul Iqmal Mordi and Jamaluddin Mahmud - Meon, Mohd Suhairil; Mordi, Muhammad Faizul Iqmal; Mahmud, Jamaluddin (UiTM Press, 2024)
The study quantitatively investigates the mechanical structural behavior and damage mechanisms of composite laminates under low-velocity impacts using Abaqus software. A three-dimensional Puck criterion is utilized to identify the onset of fiber failure and matrix cracking under tensile and compressive loading conditions. Two progressive damage evolution models are implemented to simulate damage propagation during impact. The model also incorporates cohesive elements with a bilinear traction-separation law to represent interlaminar damage.